2007
DOI: 10.1590/s1516-35982007000500002
|View full text |Cite
|
Sign up to set email alerts
|

Manejo de Paspalum dilatatum Poir. biótipo Virasoro. 1. Produção, composição química e persistência

Abstract: RESUMO -Objetivou-se avaliar o efeito da altura (10 e 20 cm) e do intervalo de cortes (30 e 45 dias) na produção de MS, na composição química e na persistência do capim-melador (Paspalum dilatatum Poir. biótipo Virasoro) em condições de campo. As plantas foram cortadas nove e seis vezes, respectivamente, nos intervalos de corte de 30 e 45 dias, no período to the stems + inflorescences.Key Words: cutting, dallisgrass, fiber, protein IntroduçãoNo bioma Campos Sulinos, que abrange o Sul do Brasil, parte da Argent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Several polyploid biotypes, including sexual tetraploids, apomictic pentaploids and hexaploids have been described (Casa et al 2002). Valued for its vigour, dallisgrass produces yields of up to 15 tons of dry matter per hectare (Cook et al 2005) with crude protein concentrations of up to 18.6 % (Baréa et al 2007). It can withstand heavy grazing and is somewhat tolerant to frost and water stress (Hutton and Nelson 1968; Robinson et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Several polyploid biotypes, including sexual tetraploids, apomictic pentaploids and hexaploids have been described (Casa et al 2002). Valued for its vigour, dallisgrass produces yields of up to 15 tons of dry matter per hectare (Cook et al 2005) with crude protein concentrations of up to 18.6 % (Baréa et al 2007). It can withstand heavy grazing and is somewhat tolerant to frost and water stress (Hutton and Nelson 1968; Robinson et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Forage concentrations of ADF in the present study were comparable with values reported elsewhere in the literature, averaging 34.2 and 39.6% in 2007 and 2008, re-spectively, across stocking treatments and 28-d periods. Baréa et al (2007) reported ADF concentrations in dallisgrass of 44.9, 45.8, and 40.6% during spring, summer, and fall, respectively, when forage was clipped at 30-d intervals, and 46.8, 46.1, and 42.4% during spring, summer, and fall, respectively, when clipped at 45-d intervals. Acosta et al (1996) reported concentrations of ADF in dallisgrass of 38.8, 39.7, 35.8, and 31.3% during spring, summer, fall, and winter, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…More recent studies have evaluated extensive collections of these species, particularly P. urvillei (Ferreira et al, 2020;Sawasato et al, 2008) and P. flavescens (Sandro et al, 2019), showing that genetic variability and breeding potential of these species is far greater than initially perceived. Most agronomic characterizations of sexual tetraploids have focused on P. flavescens (Venuto et al, 2003) and P. plurinerve (Baréa et al, 2007;da Costa et al, 2003) probably because they have been considered the most promising and morphologically similar to the well-known and extensively evaluated apomicts. These two biotypes also differ significantly in cycle length (unpublished data) and seed dormancy (Glison et al, 2015).…”
mentioning
confidence: 99%